Chronic Autoimmune Epithelitis Sjogren's Syndrome and Other Autoimmune Diseases of the Exocrine Glands - Maślińska, Maria (Rheumatology, 2019)
Epithelial tissue does not spring to mind as an obvious source of autoimmune phenomena. Yet, genetic predisposition and influence of various environmental and epigenetic factors may lead to epithelium becoming a springboard for the development of autoimmune diseases, such as Sjögren's syndrome, primary biliary cholangitis, autoimmune pancreatitis, or IgG4-related diseases. This book is intended as an introduction to the problem of "autoimmune epithelitis" and diseases closely related to the immune disturbances of the epithelium, with special emphasis on those affecting exocrine glands. Both theoretical and practical knowledge, presented by authors from a wide range of medical specialties, should be of help for medical professionals who have to deal with this difficult problem in their daily practice.